Relict montane forests from Kañaris (Lambayeque, Peru) - Llatas-Quiroz, Santos (2005)
In Kañaris (Lambayeque Department) there are enormous relic forests, probably the largest relic forests on the western slope of the Andes in Peru. They are very well preserved, but at the same time botanically virtually unexplored. These forests are found at elevations of 1500-3000 m in the highlands of Upaypiteq and the adjacent areas in the Cordillera Occidental on the atlantic slope [Shin Shin, San Lorenzo, Huacapampa, Pandachí, Gramalote, Walte, Mollepampa in the district of Kañaris (2300 m)] and on the Pacific slope [Chiñama and Luto]. The current study was undertaken with the aim of studying these forests with botanical sampling, and the life and structures of the components of the forests of Upaypiteq. The botanical specimens are the basis for progress and the pricipical forest components of the cloud forest are determined as members of: Lauraceae (Persea, Ocotea, Nectandra), Cunoniaceae (Weinmannia), Podocarpaceae (Podocarpus), Cecropiaceae (Cecropia), Myrtaceae (Myrcianthes), Moraceae (Ficus), Rubiaceae (Cinchona), Bignoniaceae (Tabebuia), Arecaceae (Ceroxylon) and tree ferns of the genus Nephelea. Additionally numerous shrub genera are present such as Miconia, Munnozia, Baccharis, Senna, Colignonia, Gaiadendron, Oreopanax, and also numerous epiphytes and lianas from families such as Bromeliaceae, Orquidaceae, Heliconiaceae, Araceae, and numerous mosses. The forest floor is covered by a complete carpet of herbaceous ferns, fungi, liverworts, liquens, Balanoforaceae and Begonia. The floristic composition is most similar to the Bosque de Cutervo and the forests of the eastern slope of the Andes and less so to the other relict forests on the western slope. These forests must be preserved, both for reasons of protecting the hydrological ressources and their wealth on incalculable phytogenetic ressources.